Eucalyptus globulus bark as a source of polyphenolic compounds with biological activity - Da Mota, MIF
Eucalyptus globulus bark, one of the main by-products of the pulp and paper industry in Southern Europe, is a potential source of valuable chemicals. In this work, chemical composition of E. globulus bark was studied with detail, including its carbohydrate composition. Response surface methodology (RSM) modeling and optimization was developed for the selective extraction of polyphenolic material from E. globulus bark. The RSM method was based on the Box-Behnken design, aiming to obtain the optimal combination of extraction conditions considering the parameters ethanol percentage in the extraction medium, temperature and time. Conditions for maximum of polyphenols in the extract are 52% ethanol, extraction temperature of 82.5°C and extraction time of 264 min. The polyphenolic compounds - quantified as gallic acid equivalents - in the extract produced at the optimal conditions was 32%, corresponding to about 2% of bark weight, with a carbohydrate co-extraction of about 1.6% of bark carbohydrate content. Some of the extracts revealed low values of IC50 against human breast cancer cells, indicative of high biological activity. This work has demonstrated the potential of E. globulus bark as a source of polyphenolic compounds with anti-proliferative activity and gives a positive contribution to the increase in products portfolio diversification in pulp industry and biorefineries.